Eco-Philosophy dan Implikasinya dalam Politik Hukum Lingkungan di Indonesia - Nurmardiansyah, Eko (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2014)
Environmental crisis is rooted in a fundamental mistake of philosophical understanding or worldview (weltanschauung) on human nature, nature, and human’s place in the overall ecosystem. The solution cannot be approached only technically and partialy, but instead, in a more comprehensive-holistic way by radically changing the perspective and the nature of human behaviour, which means, they are to be tuned in to the environmental ethics. Accordingly, human behaviour is to be conceived of and conducted in line with eco-philosophy. Its political praxis is to be implemented by way of politics of law (rechtspolitiek), politics of environmental law in particular. The politics of environmental law is the policy direction to be set by the government so as to achieve the goals and objectives in the protection and the management of the environment. This, in turn, can only be implemented if the constitution as well as the legislation is already ‘green’.